Maktens manifestation i rummet : En analys av rummens struktur och dynamik i Hrafnkels saga - Kasper, Vanessa (Helsingin yliopisto, 2020)
This study explores the spatial structure of power and its dynamics in Hrafnkels saga. The focus lies on how power is manifested and dynamized in space and how the characters place themselves in that spatial structure. Further, this study aims to investigate how well Lotman’s spatial models and theories can be applied to an Icelandic saga. The material consists of the Swedish translation of the saga Islänningasagorna: Samtliga släktsagor och fyrtionio tåtar (2014). Hrafnkels saga is popular amongst researcher, not least due to its simple structure and plot. The saga tells the story of Hrafnkell, a powerful chieftain from eastern Iceland, who loses his power and regains it six years later. Power is an eminent theme in Hrafnkels saga and in the sagas of Icelanders in general. Power is a complex construct comprised of honour, wealth and virility. Thus, someone’s power is dependent on all these components and the interaction between them. Even slight changes within the construct can have a big impact on someone’s status in society. In order to identify the spatial structure of power, a combination of Lotman’s spatial models and semiotic theories is applied to the saga. With the help of the models and theories, spatial structures, borders, elements and the dynamics between them can be identified. They also enable the detection of eventful and uneventful texts as well as mobile and immobile characters within these texts. The analysis shows that the spatial structure of power in Hrafnkels saga is built on two dimensions (up-down and west-east) that undergo a cycle of destruction and reconstruction within three subsemiospheres. The mobile characters Einarr, Sámr, Þorkell and Þorgeirr Þjóstarsson as well as Hrafnkell cross borders and spur the dynamics of power, which leads to a shift in power. The crossing of the borders is only possible with the help of certain recurring, immobile characters that manipulate the mobile characters. The manipulation itself is bound to a system of cycles that consist of recurring elements ...